Perancangan Alat Talent Identification Aspek Quickness Berbasis IOT - Abdul Manan; Dery Rimasa; Hikmat Kodrat (Fakultas Teknik Universitas Cenderawasih, 2024)
The sport of fencing is centered on skill tactics like cutting, stabbing, or using hand agility to parry an opponent's sword. In fencing, athletes must have strong reflexes and focus in order to both attack and evade attacks from opponents. An LED lamp, a buzzer, and an ultrasonic sensor were used in the tool's design. When the athlete runs toward the sensor—which is identified by a buzzer that sounds and an LED that illuminates—the gadget functions as follows: the athlete waves his hand at the sensor. The distance between the instruments is positioned according to the athlete's needs and skill level. The website that has been developed will show the ultrasonic sensor's detecting findings. The website's architecture allows for multiple tool function configurations, including training mode, tool delay, tool duration, tool detection distance, and indicators of the number of connected sensors. When the tool's durability was tested against distance, it was found to be able to establish a connection between the client and server up to 20 meters away with an average connected time of 27.39. The tool's delay test yields an average of 14.57 seconds. an average of 0.078 when the tool's point inaccuracy is tested.